2019
DOI: 10.29122/jsti.v16i3.3417
|View full text |Cite
|
Sign up to set email alerts
|

Bencana Kabut Asap Akibat Kebakaran Hutan Dan Lahan Serta Pengaruhnya Terhadap Kualitas Udara Di Provinsi Riau Februari – Maret 2014

Abstract: Analysis of land and forest fire has been conducted in relation with smoke haze disaster in Riau province during February and March 2014. Daily hotspot data from NOAA 18 and daily ISPU (Standard Air Pollutant Index) data of the ministry of environment are used in this study. Air quality has been categorized as dangerous for several days with ISPU exceeding 500. The number of hotspot indicating the forest fire reaches 2543, with 1319 hotspots detected in February 2014 and 1224 hotspots in March 2014. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…The 2014 haze event in Riau, attributed to forest fires, was marked by a record-high 1,319 hotspots. Additionally, the smog deteriorated air quality to hazardous levels, with an ISPU value exceeding 500 (Mulyana, 2019). Furthermore, one study indicated the difficulty in prosecuting arsonists due to the lack of evidence (Latif & Munir, 2017).…”
Section: Forest Fires and Air Pollutionmentioning
confidence: 99%
“…The 2014 haze event in Riau, attributed to forest fires, was marked by a record-high 1,319 hotspots. Additionally, the smog deteriorated air quality to hazardous levels, with an ISPU value exceeding 500 (Mulyana, 2019). Furthermore, one study indicated the difficulty in prosecuting arsonists due to the lack of evidence (Latif & Munir, 2017).…”
Section: Forest Fires and Air Pollutionmentioning
confidence: 99%
“…Dikutip dari www.kompas.com (2019) berbagai upaya pemerintah dalam mencegah terjadinya kebakaran hutan di Provinsi Riau yaitu dengan melakukan water bombing, menyediakan masker gratis, meliburkan aktivitas sekolah, tetapi hal tersebut bukan solusi yang tepat untuk jangka panjang [9]. Tindakan yang tegas dan nyata seperti penegakan hukum, dan diperlukan sistem alarm kebakaran yang dapat berfungsi sebagai sistem peringatan dini [16]. Dalam pengembangan sistem peringatan dini, diperlukan hasil dari Data Mining yang akurat dan dapat digunakan untuk memberikan informasi yang efektif dalam pencegahan kebakaran hutan.…”
Section: Pendahuluanunclassified
“…Pengurangan emisi dari sektor kehutanan dilakukan melalui pencegahan dan pengurangan kebakaran hutan dan lahan (karhutla), Gerakan Rehabilitasi Nasional, gerakan penanaman pohon, penerapan Reducing Emissions from Deforestation and Forest Degradation (REDD+), pencegahan penebangan liar, dan pelaksanaan Sustainable Forest Management (SFM) (Bisjoe dan Muin 2015). Pengurangan karhutla bertujuan untuk mengurangi kabut asap dan emisi karbon sehingga meningkatkan kualitas udara (Mulyana 2019). Program penanaman pohon maupun reforestasi hutan di kawasan tropis merupakan salah satu upaya untuk mitigasi dampak perubahan iklim menggunakan kemampuan penyerapan dan penyimpanan karbon oleh pohon (Locatelli et al 2015).…”
Section: Pendahuluanunclassified